Penegakan Hukum Pada Pelanggaran Rambu Lalu Lintas Oleh Kalangan Remaja - Kezia Caterina Doren Junior; Diah Imaningrum. S; Celina Tri Siwi K (Comprehensive Law Journal, 2023)
The research that the author conducted aims to find out law enforcement and the obstacles carried out by the Traffic Police Unit of Klojen Malang on Violations of Traffic Signs by Teenagers. Based on the analysis of data and facts obtained by the author directly from the Malang Klojen Police Traffic Unit, the author concludes that the law enforcement carried out by the Malang Klojen Police Traffic Unit is in the form of coaching efforts (preemptive), counseling efforts (preventive) and action efforts (represive), where the three efforts are a unity in enforcing the law on teenagers to be more orderly in driving. As for the obstacles experienced by Satlantas Klojen Malang Police when carrying out Law Enforcement, these obstacles are in the form of internal and external factors, for the internal obstacles themselves lack of law enforcement professionalism while the external obstacles are the lack of supporting facilities and infrastructure and the lack of legal awareness among teenagers. For the method used, using empirical juridical methods where this method is carried out by observation and data collection by interviewing the intended respondents.The author's suggestion is, considering that violations of traffic signs committed by teenagers are increasing, the police especially the Klojen Malang Police Traffic Unit, are more active in enforcing traffic regulations so that in the following year the number of violations of traffic signs committed by teenagers can decrease. So that efforts are made by conducting socialization in schools, colleges and in places frequented by teenagers.